PENERAPAN MANAJEMEN KELAS DALAM MENINGKATKAN PARTISIPASI ANAK-ANAK DI TPQ DAN SD NAGARI KOTO ANAU TAPAN - zafitri, ociana; Wisda, Rini Syevyilni; Samin, Samin (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
This research aims to create optimal learning conditions and neutralize the situation if disturbances occur in the classroom during the teaching and learning process, especially at TPQ and SD Koto Anau Tapan. The method used is a qualitative approach through case studies. The data collection techniques used are 1. Documents 2. Interviews 3. Observation. The results of this research show that the lack of independence of students in learning activities indicates excessive dependence. The lack of a pleasant and conducive learning atmosphere and the extent of students' interest in learning at Koto Anau Tapan is unknown, which can affect their participation and achievement.